O que se vê na TV: análise do fluxo da programação da Rede Globo - Fantinatti, Maria Sílvia (2008)
Programs and programming of Globo Television Network are analyzed in this paper in order to categorize different programs and understand the sense of the flow as a whole. The work also identifies the spaces where the network gives more room to creativity, testing new television languages. The corpus is the basic programming, considering one week, in the period of 2006 and 2007, studied through theories that match the audiovisual systems of communication. To search the meaning of programs and programming, we relied on the concepts of Analysis of Issue, Analysis of Text, Semiotics and Communication Semiology. Because of the high audience rates and the firm presence in the daily life of Brazilians, we postulate it is relevant to take a more attentive look over the programming strategies and the communication contracts that TV Globo proposes